EVALUASI DATA PULAU KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Destarina, R; Ardi, C S; Hanafi, Hanafi (UI Scholars Hub, 2017)
The availability of a complete, accurate and up to date islands’ data and information can be a reference for the government in developing the potential of islands in Indonesia. National Team for Standardization Topographic Names (TNPNR) has standardized a number of 13.466 names in the Indonesian island Gazetteer in 2013, including 35 islands in East Lombok. A validation activity through field survey which was conducted in 2016 discovered the discrepancies in toponyms or existing status of several islands in the East Lombok. The wrong toponyms refer to a location that is completely different from the one requested. Therefore, it has fatal consequences and can hinder development. As a follow up, verification and standardization of islands’ name is conducted, which was attended by the Ministry / Agency member of TNPNR as well as the local government. Results of verification set forth in the official report stating that evaluation and correction of the data islands in East Lombok has been conducted, including adjustments of toponym, status and amount to 43 islands.